Pengaruh Plastisizer Minarex Terhadap Sifat Dan Morfologi Material Wood Plastic Composite Berbasis Batang Sawit - Ady Maulana; Bahruddin Bahruddin; Ida Zahrina (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Oil palm stem is solid waste in oil palm plantation.Oil palm stem content high cellulose which not much in use with optimal. Oil palm stem have potential for filler in wood plastic composite (WPC). The aim of the research is to study the effect of content of oil palm stem particle (SBS) and content of minarex on the morphology and properties of WPC based on a mixture of oil palm stem particle (SBS) and polypropilene (PP). Ratio used of SBS/PP is 70/30, 60/40 and 50/50 with sizes of the SBS is 60-100 mesh. As plastisizer was use minarex-H with values of 0%, 2% and 10% mash. As compatibilizer was use maleated anhydrid polypropilene (MAPP) of 5% mass. WPC samples were prepared using Rheomix 3000 HAAKE mixer at temperature of 170oc. Rotor speed of 60 rpm and time of 20 minutes. Physical testing of WPC focused in water content, bulk density, water absorption and thickness swell and mechanical testing of WPC focused in tensile strength, flexural strength. Beside that morphology testing of WPC using scanning electron microscope (SEM). The result showed ratio of SBS/PP and high content of minarex in WPC will degradate of properties of WPC. The best mechanical properties of WPC are on SBS/PP mass of 50/50 for tensile strength, 61,57 kg/cm2 and SBS/PP mass of 60/40 for flexural strength, 2,68 kg/cm2. key Words : Maleated Anhydrid PolyPropylene, Morphology, plastisizer minarex, Polypropylene, Oil Palm Stem.